A critical evaluation of the spherical constant volume vessel method for determining laminar burning velocity - Rallis, Costa John (My University, 2015)
The objectives of combustion research are considered and attention directed to laminar flames, the burning velocity of which is recognised as a basic parameter in all combustion problem s. Various methods of determining this property are critically reviewed and, as a result, it is concluded th at the spherical constant volume vessel technique is potentially one of the most versa tile and accurate. However this method does not appear to have been extensively used, probably because the available equations virtually relegate it to the status of a constant pressure technique
A Thesis Presen ted in Fulfilm ent of the Requirem ents for the Degree of Doctor of Philosophy in Engineering August 1963
Keywords: Combustion, Research; Flame, Research